Extended reality technologies in adult basic life support education: A scoping review - Nino Fijačko; Špela Metličar; Boža Janžekovič; Benjamin S. Abella; Vinay M. Nadkarni; Todd P. Chang; Robert Greif (Resuscitation Plus)
Aim: In recent years, virtual and augmented reality (VR/AR) technologies have gained increasing attention as innovative tools for education, including in the field of adult Basic Life Support (BLS). While existing reviews on this topic primarily focus on comparing VR/AR with other educational approaches, our research aimed to identify the VR/AR hardware and software applications assessed in published studies and their alignment with learning objectives in adult BLS education. Methods: We conducted a scoping literature review using the Population, Exposure, and Outcome (PEO) framework to analyse publications from 2018 to 2024. The review focused on the impact of VR/AR (exposure) on affective, behavioral, and cognitive learning outcomes (outcome) in adult BLS education among laypersons, healthcare professionals, pre-licensure students, and duty-to-respond laypersons (population). Results: From 1,282 database records and 54 alternative sources, 31 articles were selected for comprehensive analysis. Many of the studies (11/31; 36%) targeted pre-licensure students, such as nursing students, and laypersons (9/31; 20%), primarily high school students. Only one study focused on duty-to-respond laypersons (1/31; 3%). VR studies (24/31; 77%) were more common than AR studies (6/31; 19%), featuring a broad spectrum of ten VR headsets compared to just two types of AR headsets. Among the assessed software applications, twenty-one commercial programs were examined—sixteen designed for VR and five for AR. Most studies investigated affective outcomes (25/31; 81%), while behavioural outcomes were also commonly examined (22/31; 71%). In contrast, cognitive outcomes were explored in fewer studies (9/31; 29%). Conclusion: Our review identified several challenges in existing studies, including variability in software and hardware, diverse learning outcomes, and accessibility issues with extended reality (XR) technology. To maximize its effectiveness, XR should be aligned with specific learning objectives rather than adopted for its novelty. Prioritizing educational efficacy ensures that XR enhances learning by addressing precise gaps, ultimately improving the understanding and retention of resuscitation skills among both laypersons and healthcare professionals.